2004
DOI: 10.1152/ajpcell.00588.2003
|View full text |Cite
|
Sign up to set email alerts
|

Munc-18-2 regulates exocytosis of H+-ATPase in rat inner medullary collecting duct cells

Abstract: -Exocytic insertion of Hϩ -ATPase into the apical membrane of inner medullary collecting duct (IMCD) cells is dependent on a soluble N-ethylmaleimide-sensitive factor (NSF) attachment protein target receptor (SNARE) complex. In this study we determined the role of Munc-18 in regulation of IMCD cell exocytosis of H ϩ -ATPase. We compared the effect of acute cell acidification (the stimulus for IMCD exocytosis) on the interaction of syntaxin 1A with Munc-18-2 and the 31-kDa subunit of H ϩ -ATPase. Immunoprecipit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 28 publications
1
21
0
Order By: Relevance
“…This role of Munc18a, in contrast to the one we propose here, could either be synapsespecific or might result from the simplification of the cellular milieu -which could exalt a particular function of Munc18. By contrast, a negative regulatory role for non-neuronal Munc18 isoforms has been proposed for GLUT4 exocytosis in adipocytes (Macaulay et al, 2002;Tamori et al, 1998;Thurmond et al, 1998), insulin exocytosis in β-cells (Zhang et al, 2000), exocytosis of human platelets (Houng et al, 2003), the apical delivery of influenza virus hemagglutinin (HA) in CaCo-2 cells (Riento et al, 2000) and H + -ATPase exocytosis in rat IMCD (Nicoletta et al, 2004). More recently, it has clearly been shown that adipocytes derived from Munc18c -/-mice display an increased sensitivity to insulinstimulated fusion of GLUT4 with the plasma membrane (Kanda et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This role of Munc18a, in contrast to the one we propose here, could either be synapsespecific or might result from the simplification of the cellular milieu -which could exalt a particular function of Munc18. By contrast, a negative regulatory role for non-neuronal Munc18 isoforms has been proposed for GLUT4 exocytosis in adipocytes (Macaulay et al, 2002;Tamori et al, 1998;Thurmond et al, 1998), insulin exocytosis in β-cells (Zhang et al, 2000), exocytosis of human platelets (Houng et al, 2003), the apical delivery of influenza virus hemagglutinin (HA) in CaCo-2 cells (Riento et al, 2000) and H + -ATPase exocytosis in rat IMCD (Nicoletta et al, 2004). More recently, it has clearly been shown that adipocytes derived from Munc18c -/-mice display an increased sensitivity to insulinstimulated fusion of GLUT4 with the plasma membrane (Kanda et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Although it has been reported that, in yeast, fusion cannot proceed to the formation of the SNARE complex in the absence of Sec proteins (Bryant and James, 2001;Sato et al, 2000), it has been suggested that, in mammals, Munc18c acts as a negative regulator of GLUT4-containing vesicles in 3T3-L1 adipocytes (Kanda et al, 2005;Tamori et al, 1998;Thurmond et al, 1998). A possible role of the Munc18b isoform has been proposed in the regulation of apical membrane transport in CaCo-2 epithelial cells (Riento et al, 1998;Riento et al, 2000), exocytosis of H + -ATPase in rat inner medullary collecting-duct cells (Nicoletta et al, 2004) and in gastricacid secretion (Liu et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Immunohistochemistry demonstrated the expression of PKC-␣, PKC-␤1, PKC-, and PKC-␦ in IC of the collecting duct. 25,27 Evidence from freshly isolated OMCD IC as well as from cell culture models 19,31,54 suggests that PKC has a stimulatory effect on H ϩ -ATPase activity. In addition, our experiments indicate that intact ERK1/2 mitogen-activated protein kinases and PI3-K are required for the stimulation to occur.…”
Section: B1 Subunit Of the Vacuolar Hmentioning
confidence: 99%
“…Munc18c was reported to localize on the basal membrane where it interacts with syn4, and release of this SM protein from the basal surface by supramaximal cholecystokinin stimulation was suggested to redirect apical exocytosis to the basal membrane (Gaisano et al, 2001). Munc18b has been shown to control apical exocytosis in several epithelial cell types (Riento et al, 2000;Kauppi et al, 2002), H ϩ -ATPase insertion into the apical membrane of kidney inner medullary collecting duct cells (Nicoletta et al, 2004), and mast cell granule secretion (Martin-Verdeaux et al, 2003). Furthermore, Munc18b was recently shown to impact on amylase release from rat parotid acinar cells by controlling the interaction of the synaptotagmin-like protein Slp4-a/granuphilin with syn2 and -3 (Fukuda et al, 2005).…”
Section: Introductionmentioning
confidence: 99%